COMPARATIVE EFFICACY OF VONOPRAZAN AND PROTON PUMP INHIBITORS IN HELICOBACTER PYLORI ERADICATION BASED ON CLARITHROMYCIN SUSCEPTIBILITY: A SYSTEMATIC REVIEW AND META-ANALYSIS - SHEETHAL SRENIGARAJAN; KARTHIK VP; PARVATHAREDDY SOWMYA; KAVITHA RAMASAMY (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Due to the rising burden of Helicobacter pylori-resistant strains, specifically to clarithromycin (CAM), there is a decline in eradication rates (ERs) with proton-pump inhibitors (PPI) containing regimens. Vonoprazan (VPZ), a first-in-class potassium-competitive acid blocker, has a rapid onset, and longer, more profound acid suppression than PPIs. This systematic review and meta-analysis aims to evaluate the efficacy of VPZ versus PPI-based triple therapy in eradicating H. pylori based on clarithromycin susceptibility. Methods: A systematic search was performed using relevant MeSH terms in PubMed, Cochrane, Web of Science, and Google Scholar databases for studies comparing the efficacy of VPZ and PPI triple therapies in eradicating H. pylori, with results stratified by clarithromycin susceptibility. Studies meeting the inclusion criteria were included, and data were extracted. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. Random effects model was applied in all analyses. Results: Eight potentially eligible studies were included. Among patients with clarithromycin-resistant H. pylori strains, VPZ-triple therapy showed significant superiority to PPI-triple therapy in both randomized controlled trials (RCT) (pooled ER-75.0% vs. 49.0%; OR-3.28; 95% CI 1.62–6.66; p=0.001) and non-RCT (NRCT) (ER-82.0% vs. 42.0%; OR-4.98; 95% CI, 2.47–10.03; p<0.001) studies. For eradication of clarithromycin susceptible (CAM-S) strains in RCTs, VPZ therapy showed significant superiority over PPI therapies (ER-90.0% vs. 86.0%; OR-1.42; 95% CI, 1.02–1.98; p=0.038); however, there was no significant difference between the therapies seen in NRCTs (ER-89.0% vs. 86.0%; OR-4.30; 95% CI, 0.72–25.85; p=0.111). Conclusion: VPZ triple therapy is superior to the conventional PPI triple therapy in eradicating CAM-resistant H. pylori strains. For CAM-S H. pylori infection, VPZ is comparable to PPI triple therapy.